Mutations in RNA‐dependent RNA polymerase could be major cause of high pandemic potential of SARS‐CoV‐2: An in‐silico study - Bhawna Sharma; Bennet Angel; Annette Angel; Vinod Joshi; Shareef Mohammed Buvvaji; Neha Singh; Khushbu Kumari; Aarya Chitransh; Poorna Khaneja; Devendra Kumar (Indonesian Journal of Biotechnology, 2025)
Human coronaviruses (HCoVs) are responsible for mild common cold to severe pneumonia‐like symptoms in infected individuals. The first HCoV was HCoV‐229E, discovered in 1962 in the US, which causes moderate symptoms. Since then, HCoVs have evolved, leading to epidemics or the recent SARS‐CoV‐2 pandemic. The main objective of this study was to understand the modifications occurred and what led to the transition from mild to pandemic form. Of the viral proteins, the RNA‐dependent RNA polymerase (RdRp) plays a crucial role in viral evolution, mutation, pathogenesis and transmission; this protein was therefore analyzed using in silico tools. We observed that RdRp has shown many mutations during its transition from mild to severe forms in HCoVs, which may have affected its enzymatic activity. The RdRp of HoV‐229E and HCoV‐NL63 showed 171 mutations, while SARS‐CoV‐2 showed the presence of 312. SARS‐CoV‐2 also showed a reduction in hydrophobic amino acid compared to the other HCoVs, consequently contributing to faster replication. Although mutations in the RdRp subdomains were found, yet five conserved regions was also presence among all the seven HCoVs; the finger and thumb subdomains had one conserved region, while the palm subdomains had three. Therefore, it can be inferred that on one hand the mutations reported in RdRp appeared to be the major cause of increased virulence leading to sporadic disease outbreaks, while on the other hand the presence of five conserved regions might prove to be potential targets for the development of new antiviral drugs.